Insights into the Active Species of Nanoparticle‐Functionalized Hierarchical Zeolites in Alkylation Reactions. Issue 12 (3rd November 2014) - Grau‐Atienza, Aida; Campos, Rafael; Serrano, Elena; Ojeda, Manuel; Romero, Antonio A.; Garcia‐Martinez, Javier; Luque, Rafael
Abstract Supported iron oxide nanoparticles have been incorporated onto hierarchical zeolites by microwave‐assisted impregnation and mechanochemical grinding. Nanoparticle‐functionalised porous zeolites were characterised by a number of analytical techniques such as XRD, N2 physisorption, TEM, and surface acidity measurements. The catalytic activities of the synthesised nanomaterials were investigated in an alkylation reaction. The results pointed to different species with varying acidity and accessibility in the materials, which provided essentially different catalytic activities in the alkylation of toluene with benzyl chloride under microwave irradiation, selected as the test reaction.